Communication Technologies and their Influence on Language: A Linguist’s View - Žic Fuchs, Milena (Array, 2010)
It has become a recognized fact that the emergence and spread of new communication technologies is producing far reaching effects not only on important aspects of communication, but also on language and languages. When one views different countries (that is languages) actual usage of communication technologies can differ. Thus in Croatia the usage of mobile phones and with them SMS text messages has become one of the most dominant means of communication that far exceeds the various forms of communication found on the Internet. Linguistically speaking, SMS text messages also manifest very interesting features which again are primarily the result of the tension between what are apparently features of ‘speech’ and ‘writing’ on the one hand, and by the technological nature of mobile telephony medium on the other. The analysis of the corpus of Croatian SMS text messages uncovered quite a few unusual features from the point of view of standard, accepted grammatical notions. One of them, was without a doubt the appearance of the aorist in informal message exchanges, very much like informal everyday conversations. What is more, the aorist, or at least a past tense that looked like the aorist in form, appeared quite frequently considering its restricted use in modern Croatian. More specifically, approximately fifty messages contained this past tense in a corpus of 6000 message exchanges. Namely, the above discussion of the use of the aorist in Croatian SMS text messages shows that grammatical forms may undergo transformations of meaning and usage, and that these transformations can be directly linked to the interplay between language and various limitations of the communication technology itself.